Clinical & Labor Clinical & Laboratory markers as pr ers as predictors for se ors for severity and erity and mortality in COVID-19 - Asma Ameen Ghareeb; Sazan Moffaq Abdulaziz (Polytechnic Journal)
Backgrounds: COVID-19, a new health challenge, can be diagnosed by many laboratory biomarkers. Biomarkers became valuable for prognosis; identifying the severity and mortality of the disease in COVID-19 patients. This study aims to determine the association of clinical, demographics, and laboratory biomarkers (CRP, D-dimer, lymphocyte, and platelet) with the severity and mortality of COVID-19. Methods: Between June 1st and November 1st, 2020, 34 healthy controls and 104 COVID-19 cases were enrolled in this study. SARS-CoV-2 infection was confirmed using the real-time RT-PCR technique. All cases were analyzed for clinical, epidemiological, and laboratory biomarkers. COVID-19 cases were regrouped into mild (n=40), moderate (n=32), and severe (n=32) groups depending on the severity of the disease; it was also re-categorized into survivor (n=85) and non-survivor (n=19) groups depending on mortality. After collecting blood from participants, hematological parameters (lymphocyte and platelet) and other biomarkers (CRP and D-dimer) were measured by colter and Cobas c111, respectively. Results: For age categories and comorbidities, Statistical significance was found among COVID-19 groups. Regarding ABO, Rh, and gender, a non-significant difference was found among groups of COVID-19 patients. Cough and headache i the most common symptom in our population. SpO2 depressed more significantly in severe and moderate groups than in mild groups. Severe and moderate groups exhibit higher CRP, Ddimer, and lymphocyte percentages than control while there was a non-significant change for platelets and absolute lymphocyte counts among studies groups. All studied laboratory biomarkers were higher in non-survivors than in survivor COVID-19 groups. A significant correlation was found between D-dimer and other laboratory biomarkers. Conclusion: Gender, ABO, and Rh were not associated but age and comorbidities were associated with the severity of COVID-19. All studied laboratory biomarkers were associated with mortality.